Successful Pallidal Stimulation in a Patient with -Related Dystonia - Jun Kyu Mun; Ah Reum Kim; Jong Hyeon Ahn; Minkyeong Kim; Jin Whan Cho; Jung-Il Lee; Kyung Rae Cho; Jinyoung Youn (Journal of Movement Disorders, 2020)
Although the KMT2B gene was identified as a causative gene for early-onset generalized dystonia, the efficacy of deep brain stimulation (DBS) in KMT2B-related dystonia has not been clearly elucidated. Here, we describe a 28-year-old woman who developed generalized dystonia with developmental delay, microcephaly, short stature, and cognitive decline. She was diagnosed with KMT2B- related dystonia using whole-exome sequencing with a heterozygous frameshift insertion of c.515dupC (p.T172fs) in the KMT2B gene. Oral medications and botulinum toxin injection were not effective. The dystonia markedly improved with bilateral pallidal DBS (the Burke-Fahn-Marsden Dystonia Rating Scale score was reduced from 30 to 5 on the dystonia movement scale and from 11 to 1 on the disability scale), and she could walk independently. From this case, we suggest that bilateral globus pallidus internus DBS can be an effective treatment option for patients with KMT2B-related generalized dystonia.